An ecophysiological and developmental perspective on variation in vessel diameter - Hacke, Uwe G; Spicer, Rachel; Schreiber, Stefan G; Plavcová, Lenka (Plant, cell & environment, 2017)
Variation in xylem vessel diameter is one of the most important parameters when evaluating plant water relations. This review provides a synthesis of the ecophysiological implications of variation in lumen diameter together with a summary of our current understanding of vessel development and its endogenous regulation. We analyzed inter-specific variation of the mean hydraulic vessel diameter (Dv ) across biomes, intra-specific variation of Dv under natural and controlled conditions, and intra-plant variation. We found that the Dv measured in young branches tends to stay below 30 µm in regions experiencing winter frost, whereas it is highly variable in the tropical rainforest. Within a plant, the widest vessels are often found in the trunk and in large roots; smaller diameters have been reported for leaves and small lateral roots. Dv varies in response to environmental factors and is not only a function of plant size. Despite the wealth of data on vessel diameter variation, the regulation of diameter is poorly understood. Polar auxin transport through the vascular cambium is a key regulator linking foliar and xylem development. Limited evidence suggests that auxin transport is also a determinant of vessel diameter. The role of auxin in cell expansion and in establishing longitudinal continuity during secondary growth deserve further study.
Keywords: vascular cambium; Magnoliopsida; Plant Development; auxin; druhová specificita; freezing-induced embolism; vessel tapering; vessel development; kyseliny indoloctové; vývoj rostlin; phenotypic plasticity; Indoleacetic Acids; Xylem; xylem; xylém; biomes; Species Specificity; provenance trials